2009
DOI: 10.1128/mcb.01655-08
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction of the Ess1 Prolyl Isomerase with Components of the RNA Polymerase II Initiation and Termination Machineries

Abstract: The C-terminal domain (CTD) of the largest subunit of RNA polymerase II (Pol II) is a reiterated heptad sequence (Tyr1-Ser2-Pro3-Thr4-Ser5-Pro6-Ser7) that plays a key role in the transcription cycle, coordinating the exchange of transcription and RNA processing factors. The structure of the CTD is flexible and undergoes conformational changes in response to serine phosphorylation and proline isomerization. Here we report that the Ess1 peptidyl prolyl isomerase functionally interacts with the transcription init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
80
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(92 citation statements)
references
References 66 publications
9
80
0
3
Order By: Relevance
“…In both yeast and mammals, Pin1 (Ess1 in yeast) regulates the conformation and phosphorylation state of the RNA polymerase (RNAP) II carboxyterminal domain (CTD) (1,41). Ess1 promotes dephosphorylation of Ser-5 of the heptad repeat (Y-S 2 -P-T-S 5 -P-S) in the CTD by interactions with CTD-associated phosphatases Ssu72 and Pcf11, thereby regulating the association of the CTD with components of the 3=-end processing machinery (24,56). Yeast Ess1 is required for transcription termination of small noncoding RNAs such as snoRNAs, cryptic unstable transcripts (CUTs), and upstream regulatory RNAs (uRNAs) via the Nrd1 pathway (51).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In both yeast and mammals, Pin1 (Ess1 in yeast) regulates the conformation and phosphorylation state of the RNA polymerase (RNAP) II carboxyterminal domain (CTD) (1,41). Ess1 promotes dephosphorylation of Ser-5 of the heptad repeat (Y-S 2 -P-T-S 5 -P-S) in the CTD by interactions with CTD-associated phosphatases Ssu72 and Pcf11, thereby regulating the association of the CTD with components of the 3=-end processing machinery (24,56). Yeast Ess1 is required for transcription termination of small noncoding RNAs such as snoRNAs, cryptic unstable transcripts (CUTs), and upstream regulatory RNAs (uRNAs) via the Nrd1 pathway (51).…”
mentioning
confidence: 99%
“…Yeast Ess1 is required for transcription termination of small noncoding RNAs such as snoRNAs, cryptic unstable transcripts (CUTs), and upstream regulatory RNAs (uRNAs) via the Nrd1 pathway (51). Ess1 functionally interacts with the transcription initiation factor TFIIB, Ssu72 phosphatase, and Pta1 components of the 3=-end processing machinery to influence gene looping (24). Besides its effects on transcription, Pin1 has been implicated in the control of mRNA stability of three AU-rich element (ARE)-containing mRNAs, namely, those for granulocye-macrophage colony-stimulating factor (GM-CSF), parathyroid hormone (Pth), and transforming growth factor ␤ (TGF-␤), in the cytoplasm (10,25).…”
mentioning
confidence: 99%
“…Pin1 has been linked to a number of signaling pathways in human cells and seems to target a wide variety of proteins for isomerization (33,70). In contrast, extensive genetic studies have thus far identified only RNA polymerase II (pol II) as the target of Ess1 in yeast (21,27,65).Within the RNA pol II complex, Ess1 targets the carboxy-terminal domain (CTD) of the largest subunit, Rpb1 (38, 65), which is composed of 26 repeats of the heptapeptide Y 1 S 2 P 3 T 4 S 5 P 6 S 7 (62). Each repeat contains two potential Ess1 substrate binding sites (S-P), where the serines are known to be phosphorylated (24,43).…”
mentioning
confidence: 99%
“…The dephosphorylation of RNA polymerase II C-terminal domain (CTD) by the yeast homolog Ssu72 could be facilitated by Ess1/Pin1 peptidyl-prolyl cis-trans isomerase (Krishnamurthy et al, 2009;Werner-Allen et al, 2011). Moreover, murine Pin1 can be phosphorylated by death-associated protein kinase 1 (DAPK1), and this phosphorylation alters nuclear localization and enzymatic activity of Pin1 .…”
Section: Ectopic Expression Of Unc-44l In Epidermis Contributes To Damentioning
confidence: 99%